Impacts of the COVID-19 crisis on vegetable value chains in Ethiopia - Tamru, Seneshaw; Hirvonen, Kalle; Minten, Bart; Taffesse, Alemayehu Seyoum; Anne Bossuyt (International Food Policy Research Institute, 2020)
The COVID-19 pandemic is beginning to disrupt food value chains in Ethiopia and elsewhere, impacting the livelihoods of farmers and the diets of rural and urban households. These effects are likely to hit the poorest and most vulnerable farmers and consumers the hardest, but they are not yet well understood. More evidence is needed to guide the government and other organizations in devising responses. While not representative of the whole value chain, our interviews with vegetable production stakeholders have a number of potential policy implications.